INJURIES DURING THE COVID-19 PANDEMIC IN THE 2021 PAULISTA SOCCER CHAMPIONSHIP IN BRAZIL - Gustavo Gonçalves Arliani; Danilo José Leite Gomes; Paulo Henrique Schmidt Lara; Jorge Roberto Pagura; Moisés Cohen (Acta Ortopédica Brasileira)
ABSTRACT Objective: To assess the incidence and characteristics of injuries that occurred during the 2021 season of the Paulista Soccer Championship during the coronavirus disease 2019 pandemic and to compare these characteristics before and after the championship interruption. Methods: A prospective study was conducted using an electronic form developed by the Medical Committee of the Paulista Soccer Federation. The results were sent by the team physicians of Series A1 after each round of the Paulista Soccer Championship. Results: Series A1 presented 7.2 injuries per 1,000h of game time. Most injuries occurred within 31–45 min of the match, with muscle injuries being the most frequent and the lower limbs the most affected. Only 10% of injuries required surgery. The strikers were the most affected players and most injuries occurred in penalty-free movements. There was no statistical difference between pre- and post-interruption of the championship due to the pandemic. Conclusion: The incidence of injuries per 1,000h was below the average reported in the literature. Most injuries occurred in the lower limbs; muscle sprains were the most common type of injury, followed by sprains and fractures. MRI was the most commonly requested examination; and most injuries were classified as moderate. Overall, 10% of the injuries were treated surgically. There was no difference between pre- and post-championship interruption. Level of evidence VI, Descriptive epidemiology study.